помогите решить пожалуйста:
6-5х=-9х-2
2(5х-1)+8=6
4+5(3х-4)=7х-8
6(3х+4)-5(4х-3)=29
2х-4(7х-3)=10-5(3х-7)
11(2х-3)=5(4х-6)+2х

  • 6-5х=-9х-2      9х - 5х = -2 - 6      4х = -8     х = -2
    2(5х-1)+8=6      10х - 2 + 8 = 6    10х = 6 + 2 - 8    10х = 0  х = 0
    4+5(3х-4)=7х-8      4 + 15х - 20 = 7х - 8      15х - 7х = -4 + 20 - 8    8х = 8  х = 1
    6(3х+4)-5(4х-3)=29      18х + 24 - 20х + 15 = 29     - 2х = 29 - 39    -2х = - 10  х = 5 
    2х-4(7х-3)=10-5(3х-7)    2х - 28х + 12 = 10 - 15х + 35    2х -28х + 15х = 10 + 35 - 12
           -11х = 33    х = -3
    11(2х-3)=5(4х-6)+2х
        22х - 33 = 20х -30 + 2х      22х - 20х - 2х = 33 - 30  0х = 3  ????